Factor structure of situational decision-making ability in basic face-up situations in basketball games - Ohyama, Y.; Aoyagi, O.; Yaita, A.; Komure, I.; Tagata, S.; Nagamine, K.; Annoura, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction In a basketball game, it is important to have the ability to assess the situation in order to instantly select the best play for the situation. The ability to make decision-making momentarily is naturally based on knowledge prior to games. Moreover, it is thought that not all individual situational judgments are made independently, but that there are some common situational judgment abilities underscoring these judgments that have been cultivated through experience and other factors. Therefore, this study aimed to examine the factor structure of the situational judgment ability in basic face-up situations, which is most often found in basketball games.